Drug Utilization Evaluation of Anti-Diabetic Medication through Prescription Monitoring - Verma, Sunaina; Joshi, Yogesh; Singh, Ankita (Asian Journal of Pharmaceutical Research and Development, 2019)
Diabetes is a chronic and potentially disabling disease that represents an important public health and clinical concern. The study was designed to assess the drug utilization evaluation of anti-diabetic medications through prescription monitoring in a tertiary care hospital at capital city Dehradun in a northern state Uttarakhand. Prescriptions from patients of diabetes were selected for the study and data was collected from patients using a questionnaire format. All the necessary and relevant information will be collected from out-patient prescriptions, laboratory data reports and also by verbal communication with patients. Out of total 100 prescriptions of diabetic patients, it was found that gender wise distribution of diabetic patients was more in females (64%) as compared to males (36%). Among 100 patients, type 1 diabetes occurred in 16% patients and type 2 diabetes occurred in 84% patients. It was also analyzed that both type 1 and type 2 diabetes were mostly occurred in females. Among type 2 diabetes patients, Glimepiride were mostly prescribed in 42% patients, followed by Metformin in 22% patients and Gliclazide in 20% while in type 1 diabetes patients, Human Insulin were prescribed in 16% patients. Prescription analysis showed that maximum prescriptions (50%) contain two drugs per prescription while six drugs per prescription were shown by only 2% prescriptions. This study may provide further help to prescribers for improvement in current prescribing trends in the management of diabetes mellitus.